Internal scrambled virtual keyboard for password protection - Mahesh Kumar Reddy, P; Kavya, B; S. G. Aruna Sri, P (International Journal of Engineering and Technology, 2018)
Due to the Wide Growth of Internet the Electronic Commerce and Transactions is also Increasing. Numerous Companies have built up their web based exchanging stages Such as Banking Portals, Online Shopping, Ticket Booking and so forth. Many of these platforms are Providing Virtual Keyboard for making the Authentication of user more Secure. But the Virtual Keyboard is also having some draw-backs which the attackers make take as an advantage. A few of these consolidate Click based Screenshot Capturing and shoulder Surfing. To Maintain a strategic distance from these disadvantages, we require to outline Virtual Console which will change the Position of Keys on console for each on click activity and each key will have a fallacy value through a Rotation Pattern i.e the key which is pressed is not the actual key value, the user only knows the Actual Position of the key. So, the Screen Captures or Screen Recordings will not have the capacity to discover the Actual key. Our Proposed Framework makes the utilization of virtual console more Secured for clients through Key Rotation Technique.Â